(untitled) (Anwer Khan Modern Medical College Journal, 2023)
Background: Irritable Bowel Syndrome (IBS) is one of the most common functional gastrointestinal disorder in worldwide. Now-a-days its prevalence rate is also simultaneously increasing in Bangladesh as well. But most of the people are unaware about it as it has no significant complications. The aim of the study was to find out the Prevalence of Irritable Bowel Syndrome (IBS) & its associated risk factors among the adult Bangladeshi population in a selected Tertiary Level Hospital in Bangladesh. Materials & Methods: A descriptive cross-sectional study was conducted among the adult Bangladeshi population in a selected Tertiary level Hospital in Bangladesh from February to May, 2017 and data was collected from the respondents by using semi-structured questionnaire using face to face interview and it was analyzed by using SPSS. Results: The study revealed that mean age of the respondents was 30.7 years & almost half (49.3 %) of the respondents were educated up to HSC level. The average monthly income of the respondents was 9230.4 taka. The majority (76%) of the respondents had normal BMI. It has been seen that close to eight-tenth (77%) of the respondents were males and the rest of the respondents were females. more than half (58%) of the respondents were smokers. The findings of this study reveal that the prevalence of Irritable Bowel Syndrome (IBS) was 13.2%. More than half of the respondents had some changes in their bowel habit that is either Diarrhea/ Constipation. In this study the findings also revealed that close to three-tenth of the respondents had anxiety/stress. Conclusion: Proportion of IBS among adult Bangladeshi Population is increasing day by day & it has been seen that IBS symptoms are associated with anxiety/stress, monthly income of the respondents. The study findings demand the strategic plan for surveillance & control of Irritable Bowel Syndrome (IBS) in Bangladesh. AKMMC J 2021; 12(1) : 28-32